Analisis Penggunaan Instrument Penilaian Pemahaman Konsep dan Literasi Sains di SMA Kabupaten Solok - Dirman, Hendra Musfa; Mufit, Fatni (Universitas PGRI Semarang, 2022)
The purpose of 21-st century learning is to create students who have scientific literacy skills and conceptual understanding. One of the efforts that can be done is the use of appropriate forms of assessment instruments. The purpose of this study was to obtain a profile of the use of concept assessment instruments and scientific literacy used by physics teachers at SMA Solok Regency. This research was survey research. The respondents of this research were five senior high school physics teachers teaching in five senior high schools in Solok Regency. The data were collected using interviews and document analysis. The results showed that teachers only knew several forms of concept understanding assessment instruments. Thus, teachers have limited information in assessing students’ conceptual understanding. In addition, teachers have not been maximal in implementing scientific literacy competence in the use of assessment instruments.Keywords: Instruments, Scientific Literacy, Concept Understanding.